A circular economy approach to plastic waste - Payne, Jack; McKeown, Paul; Jones, Matthew D. (Polymer degradation and stability, 2019)
Growing environmental concerns associated with the accumulation of plastic waste in the natural environment has incentivised considerable research into renewable alternatives, and more recently, alternative waste management strategies. This review aims to introduce poly (lactic acid) (PLA), a bioplastic, and recent research within the field. Attention will then shift to research surrounding plastic waste management. Various end-of-life (EOL) options available to plastics will be discussed more broadly, before presenting existing technologies, challenges and future opportunities exclusively for PLA. Herein, all waste management strategies presented for PLA are discussed within the context of industrial feasibility. •The current and future prospects of bioplastics is discussed with emphasis on poly (lactic acid) (PLA).•The production of lactic acid and subsequent routes and mechanisms to PLA are presented with key PLA properties are outlined.•The end-of life options for plastics are discussed in the context of a circular economy.•Waste management strategies for PLA are discussed in greater detail with emphasis on chemical recycling techinqiues.